2018
DOI: 10.4174/astr.2018.95.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic fistula and mortality after surgical management of pancreatic trauma: analysis of 81 consecutive patients during 11 years at a Korean trauma center

Abstract: PurposePancreatic trauma is infrequent because of its central, deep anatomical position. This contributes to a lack of surgeon experience and many debates exist about its standard care. This study aimed to investigate the postoperative pancreatic fistula (POPF) and mortality of pancreatic trauma after operation.MethodsWe reviewed records in the trauma registry of our institution submitted from January 2006 to December 2016. The grade of pancreatic injury, surgical management, morbidity, mortality, and other cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…This multicenter nationwide survey conducted over the last decade revealed that mortality was 5% for all cases, 1.8% for patients with isolated pancreatic injury, and 3% for patients with MPD injury. This mortality rate was similar to that reported in previous studies, which found that the mortality rate is 0%‐10% 2,4,14,15 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This multicenter nationwide survey conducted over the last decade revealed that mortality was 5% for all cases, 1.8% for patients with isolated pancreatic injury, and 3% for patients with MPD injury. This mortality rate was similar to that reported in previous studies, which found that the mortality rate is 0%‐10% 2,4,14,15 …”
Section: Discussionsupporting
confidence: 91%
“…It has been previously reported that emergency PD for pancreatic injury was associated with a very high mortality rate (>30%) because of the patient's poor condition and surgical complexity. 14,25 However, compared with the outcomes of these previous reports, the outcome of PD in this recent series was excellent with zero mortality. This is presumably because the attending centers are all JSAEM board-certified hospitals that have abundant experiences in abdominal emergencies.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Our morbidity and mortality rates are in agreement with the available literature, which shows similar or higher morbidity and mortality, particularly with increasing injury grades and hemodynamic instability. 2,7,11,31 Among the limitations of this study is the relatively small number of patients. Likewise, lack of interventional management using pancreatic duct stenting could have avoided the need of surgical intervention in a substantial number of patients.…”
Section: Discussionmentioning
confidence: 94%
“…5 Pancreatic trauma might trigger several consequences including pancreatic leaks, abscesses, pseudocysts, pancreatitis and pancreatic necrosis. [6][7][8][9][10] The risk of complications and mortality should be considered with extensive parenchymal and ductal injuries as well as when the diagnosis is delayed. 11,12 Evaluation of the extent of pancreatic injury by various imaging techniques in the setting of abdominal trauma might be demanding.…”
Section: Introductionmentioning
confidence: 99%